Elkanah Billings: The Lawyer Who Revealed the Ancient Life of the Past - Minicucci, Jeffrey (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2016)
Elkanah Billings is an important, historical example of a 19th century Ontario lawyer who made a contribution to Canadian life by engaging in a pursuit outside the practice of law. An accomplished autodidact (i.e. a self-taught expert) and renowned as the father of Canadian paleontology, Billings has the distinction of being claimed by the global paleontological and geological professional communities, and by the Ontario legal profession. Although some researchers have alleged that Billings had abused alcohol during his life, he nonetheless managed to establish a remarkable career as a paleontologist. He applied the researching, analytical, and argumentative skills that he had acquired during his years of training and practice as a lawyer to the science of paleontology enabling him to peel back the layers of time to reveal the ancient life of the past. In view of his strengths, weaknesses, and professional accomplishments, the example of Billings' history potentially becomes increasingly relevant in the effort to reinforce the importance of ethics and professional responsibility among earth science and evolutionary biology professionals and to promote a shared sense of professional community and heritage. The example of Billings' history also presents a golden opportunity for the synthesist to nurture a closer connection between the law and science in the form of interdisciplinary or multidisciplinary dialogue and collaboration.